Modified sodium ion battery positive electrode material and preparation method thereof, sodium ion battery
By the tunnel phase and spinelite phase of the O3 sodium ion battery orthode material, combined with the double -layer overflow structure of NA3RUO4, the lack of the material in the ion transmission rate and structural stability of the material, significantly improved, significantly improved, significantly improved, significantly improved The electrical performance and cycle stability of the battery.
Patent Information
- Application Number
- CN202411322193.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The positive electrode material of O3 type sodium ion battery has shortcomings in terms of ion transfer rate and structural stability, especially during the charging and discharging process, which leads to irreversible slippage of the transition metal layer.
[NAXLI0.44-X] [MNYLI1-Y] O2 with tunnel phase and spinels is used to cover the modification of O3 phase sodium transition metal oxide matrix, and further uses NA3RUO4 as the second coating to form formed Double -layer composite modification structure.
It improves the ion conduction and structural stability of the matrix material, improves the electrical performance and cycle stability of the battery, and ensures the transmission rate of sodium ions and the long cycle life of the material.
Smart Images

Figure CN118867209B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and particularly relates to coating modification of sodium ion battery positive electrode materials. Background Art
[0002] Ni in the positive electrode material of O3 type sodium ion battery 2+ / Ni 3+ / Ni 4+ Due to its high redox potential, it has a high operating voltage and specific capacity, and is considered to be an ideal cathode material for sodium-ion batteries. However, its ion transport rate is not ideal, and it is easy to be in a de-sodium state during the charge and discharge process, which leads to irreversible slip of the transition metal layer and affects the structural stability of the material.
[0003] Currently, coating strategies are often used to improve these problems. However, these methods either require complex synthesis processes to obtain coupling between the coating layer and the matrix material, or the coating layer material has a single function and cannot improve the transport of sodium ions. Summary of the invention
[0004] In response to the above technical problems, the present application provides a modified sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery.
[0005] To achieve the above objectives, this application proposes the following technical solutions:
[0006] In a first aspect, a modified sodium ion battery positive electrode material is provided, comprising an O3 phase sodium transition metal oxide matrix and a coating layer 1 located on at least a portion of the surface of the matrix, wherein the coating layer 1 has a tunnel phase and a spinel phase, and the chemical formula of the coating layer 1 is [Na x Li 0.44-x ][Mn y Li 1-y ]O2, where 0.39≤x≤0.4, 0.03≤y≤0.06.
[0007] Preferably, it further includes a coating layer 2, and the substrate, the coating layer 1 and the coating layer 2 are arranged in sequence from the inside to the outside.
[0008] Preferably, the coating layer 2 is Na3RuO4.
[0009] Preferably, the chemical formula of the O3 phase sodium transition metal oxide matrix is NaNi a Fe b Mn 1-a-b O2, 0.2≤a≤0.5, 0.1≤b≤0.4.
[0010] Preferably, the mass of the coating layer 1 is 0.5-1% of the mass of the O3 phase sodium transition metal oxide matrix.
[0011] Preferably, the mass of the coating layer 2 is 0.5-1% of the mass of the O3 phase sodium transition metal oxide matrix.
[0012] In a second aspect, a method for preparing a modified sodium ion battery positive electrode material is provided, comprising:
[0013] S1, adding a sodium source, a lithium source, a manganese source and citric acid into ethanol, stirring to obtain a solution A; in step S1, the molar ratio of sodium in the sodium source to lithium in the lithium source and manganese in the manganese source is 0.39-0.4:0.98-1.02:0.03-0.06;
[0014] S2, adding O3 phase sodium transition metal oxide to solution A, stirring for a period of time, heating and stirring until the solvent is evaporated to obtain a solid, and drying the solid to obtain a mixture B;
[0015] S3. Sinter the mixture B at 900-950° C. to obtain a sodium ion battery positive electrode material coated with the coating layer 1.
[0016] Preferably, after step S3, the method further comprises the step of continuing in-situ coating with Na3RuO4 for modification;
[0017] The in-situ coating Na3RuO4 modification specifically includes:
[0018] (1) Adding a sodium source and a ruthenium source into ethanol and stirring to obtain a solution C;
[0019] (2) adding the modified sodium ion battery positive electrode material obtained in step S3 to solution C, stirring for a period of time, and then heating and stirring until the solvent is evaporated to dryness to obtain a solid, and drying the solid to obtain a mixture D;
[0020] (3) Calcining the mixture D to obtain a further modified sodium ion battery positive electrode material.
[0021] Preferably, in step S1, the molar amount of citric acid is 1 to 1.5 times the molar amount of the manganese source.
[0022] Preferably, the mass of the coating layer 1 is 0.5-1% of the mass of the O3 phase sodium transition metal oxide.
[0023] Preferably, in step S3, the sintering time is 10 to 12 hours.
[0024] Preferably, in step (1), the molar ratio of sodium in the sodium source to ruthenium in the ruthenium source is 3-3.3:1.
[0025] Preferably, in step (1), the mass of Na3RuO4 prepared by the sodium source and the ruthenium source is determined to be 0.5-1% of the mass of O3 phase sodium transition metal oxide.
[0026] Preferably, in step (3), the calcination temperature is 600-650° C. and the calcination time is 20-25 h.
[0027] In a third aspect, a sodium ion battery is provided, comprising the aforementioned modified sodium ion battery positive electrode material or the modified sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0028] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects:
[0029] Using [Na x Li 0.44-x ][Mn y Li 1-y ]O2 coating and modification of the O3 phase sodium transition metal oxide matrix can improve the ion conductivity and structural stability of the matrix material, thereby improving the electrical performance and cycle stability of the battery.
[0030] Further coating modification with Na3RuO4 can provide a sodium source to ensure that the sodium ions in the lattice structure are not consumed, thereby ensuring the stability of the structure and improving the electrical performance of the battery.
[0031] Double-layer composite modification is beneficial to further improve the electrical performance and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is the XRD pattern of the positive electrode material prepared in Example 1.
[0034] Figure 2 This is the SEM image of the positive electrode material prepared in Example 1.
[0035] Figure 3 This is the XRD pattern of the first coating layer.
[0036] Figure 4 This is an enlarged view of the characteristic peaks of the crystal plane of the first cladding layer (350).
[0037] Figure 5This is an enlarged view of the characteristic peaks of the crystal plane of the first cladding layer (140).
[0038] Figure 6 The positive electrode materials and NaNi prepared in Examples 1-4 and Comparative Example 1 0.5 Fe 0.4 Mn 0.1 Cycling curves of the battery assembled with O2. DETAILED DESCRIPTION
[0039] The present invention provides a modified sodium ion battery positive electrode material, comprising an O3 phase sodium transition metal oxide matrix and a coating layer 1 located on at least a portion of the surface of the matrix, wherein the coating layer 1 has a tunnel phase and a spinel phase, and the chemical formula of the coating layer 1 is [Na x Li 0.44-x ][Mn y Li 1-y ]O2, where 0.39≤x≤0.4, 0.03≤y≤0.06. The [Na x Li 0.44-x ][Mn y Li 1-y ]O2 is used to coat and modify the O3 phase sodium transition metal oxide matrix, and the tunnel phase has a special S-type structure, which is beneficial to enhance the Na + The diffusion dynamics of the spinel phase have three-dimensional Li + Diffusion channel, its theoretical capacity is high and the cost is low. + Replacement of Mn 3+ It can strengthen the crystal structure through Li-O bonds, provide a stable crystal framework, destroy the Mn-Mn interaction, and hinder the Mn 3+ disproportionation, reducing the GEM distortion, thereby reducing the dissolution of Mn and extending the cycle life.
[0040] In some preferred embodiments, a coating layer 2 is further included, and the substrate, coating layer 1 and coating layer 2 are arranged in sequence from the inside to the outside. Preferably, the coating layer 2 is Na3RuO4. Na3RuO4 is further used as the second coating layer. This material has 3 moles of sodium per unit molecular formula, and it sacrifices itself under high potential to produce Na by oxidation decomposition. +ions, compensating for the sodium consumption caused by the formation of the positive and negative electrode interface film. For O3-type transition metal oxide positive electrode materials, additional sodium sources can ensure that the sodium ions in the lattice structure are not consumed, ensuring the stability of the positive electrode material, thereby showing good electrochemical performance in long-cycle tests; and Ru in Na3RuO4 is +5 valence, with a high covalent Ru-O bond and a high Na / Ru ratio. During the decomposition of sodium ions, the specific Na-O-Na configuration tends to form a non-bonded O 2p state, that is, a stable peroxide OO bond is formed during charge and discharge, which can effectively inhibit the collapse of the structure. And the double-layer coating structure can effectively play a variety of roles, not only can it better combine the advantages of O3, spinel phase and tunnel-type three-phase, improve the discharge specific capacity of the positive electrode material, accelerate the transmission rate of sodium ions, but also supplement sodium ions for the core material and enhance the cycle stability of the material.
[0041] In some preferred embodiments, the chemical formula of the O3 phase sodium transition metal oxide matrix is NaNi a Fe b Mn 1-a-b O2, 0.2≤a≤0.5, 0.1≤b≤0.4.
[0042] In some preferred embodiments, the mass of the coating layer 1 is 0.5-1% of the mass of the O3 phase sodium transition metal oxide matrix.
[0043] In some preferred embodiments, the mass of the coating layer 2 is 0.5-1% of the mass of the O3-phase sodium transition metal oxide matrix.
[0044] The present invention provides a method for preparing a modified sodium ion battery positive electrode material, comprising:
[0045] S1, adding a sodium source, a lithium source, a manganese source and citric acid into ethanol, stirring to obtain a solution A; in step S1, the molar ratio of sodium in the sodium source to lithium in the lithium source and manganese in the manganese source is 0.39-0.4:0.98-1.02:0.03-0.06;
[0046] S2, adding O3 phase sodium transition metal oxide to solution A, stirring for a period of time, heating and stirring until the solvent is evaporated to obtain a solid, and drying the solid to obtain a mixture B;
[0047] S3. Sinter the mixture B at 900-950° C. to obtain a sodium ion battery positive electrode material coated with the coating layer 1.
[0048] In some embodiments, in step S1, the sodium source is one or more of sodium carbonate, sodium acetate, sodium oxalate, sodium bicarbonate, sodium nitrate, and the like.
[0049] In some embodiments, in step S2, the lithium source is one or more of lithium carbonate, lithium acetate, lithium oxalate, lithium hydroxide, lithium nitrate, and the like.
[0050] In some embodiments, in step S1, the manganese source can be a conventional oxide in the art or a manganese source that can be decomposed into an oxide, and can be a soluble or insoluble manganese source, for example, one or more of manganese carbonate, manganese acetate, manganese oxalate, manganese nitrate, and the like.
[0051] In some preferred embodiments, after step S3, a step of continuing modification is further included, that is, continuing to in-situ coat Na3RuO4; the Na3RuO4 coating adopts an existing method, specifically including:
[0052] (1) Adding a sodium source and a ruthenium source into ethanol and stirring to obtain a solution C;
[0053] (2) adding the modified sodium ion battery positive electrode material obtained in step S3 to solution C, stirring for a period of time, and then heating and stirring until the solvent is evaporated to dryness to obtain a solid, and drying the solid to obtain a mixture D;
[0054] (3) Calcining the mixture D to obtain a further modified sodium ion battery positive electrode material.
[0055] In some preferred embodiments, in step S1, the molar amount of citric acid is 1 to 1.5 times the molar amount of the manganese source.
[0056] It is worth noting that in step S2, the temperature of heating and stirring is higher than the volatilization temperature of the solvent. In order to improve the uniformity of mixing of the substances in the system, the heating temperature should not be too much higher than the volatilization temperature of the solvent to avoid volatilization too fast resulting in a poor mixing effect of the substances. However, the temperature can be conventionally controlled, for example, 80 to 120 ° C. In this step, the stirring speed can also be conventionally controlled, as long as a good stirring and mixing effect can be achieved for the reaction system. In this step, the drying method can adopt a conventional drying method, such as vacuum drying, and the drying temperature can also be conventionally controlled, for example, 60 to 80 ° C.
[0057] In some embodiments, in step (1), the sodium source can be a conventional sodium source in the art, specifically one or more of sodium acetate, sodium carbonate, sodium oxalate, sodium bicarbonate, sodium nitrate, and the like.
[0058] In some embodiments, in step (1), the ruthenium source can be a conventional oxide in the art or a ruthenium source that can be decomposed into an oxide, and can be a soluble or insoluble ruthenium source, for example, at least one of ruthenium dioxide, ruthenium oxalate, and the like.
[0059] In some preferred embodiments, the mass of the coating layer 1 is 0.5-1% of the mass of the O3 phase sodium transition metal oxide.
[0060] In some preferred embodiments, in step S3, the sintering time is 10 to 12 hours.
[0061] In some preferred embodiments, in step (1), the molar ratio of sodium in the sodium source to ruthenium in the ruthenium source is 3-3.3:1.
[0062] In some preferred embodiments, in step (1), the mass of Na3RuO4 prepared by the sodium source and the ruthenium source is determined to be 0.5-1% of the mass of the O3 phase sodium transition metal oxide.
[0063] It is worth noting that in step (2), the temperature of heating and stirring can be higher than the volatilization temperature of the solvent. In order to improve the uniformity of mixing of the substances in the system, the heating temperature should not be too much higher than the volatilization temperature of the solvent to avoid volatilization too quickly resulting in a poor mixing effect of the substances. However, the temperature can be conventionally controlled, for example, it can be 80~120°C. In this step, the stirring speed can also be conventionally controlled, as long as it can achieve a good stirring and mixing effect on the reaction system. In this step, the drying method can adopt a conventional drying method, such as vacuum drying, and the drying temperature can also be conventionally controlled, for example, it can be 60~80°C.
[0064] In some preferred embodiments, in step (3), the calcination temperature is 600-650° C.; and the calcination time is 20-25 h.
[0065] The present invention also provides a sodium ion battery, comprising the aforementioned modified sodium ion battery positive electrode material or the modified sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0066] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0067] Example 1
[0068] Step 1: Sodium carbonate, lithium carbonate, manganese carbonate and citric acid were weighed according to the molar ratio of Na, Li, Mn and citric acid of 0.39:1.02:0.03:0.03, dispersed evenly in ethanol, and stirred for 1 h.
[0069] Step 2: Weigh the O3 phase core material NaNi according to the coating ratio of 0.5% 0.5 Fe 0.4 Mn 0.1 O2 (i.e., the target coating layer and O3 phase core material NaNi 0.5 Fe0.4 Mn 0.1 O2 mass ratio), dispersed in the solution of step 1, stirred for 1 hour, transferred to an oil bath pot and evaporated at 80°C, then taken out and dried in a vacuum drying oven at 60°C overnight.
[0070] Step 3: Place the material in step 2 in a muffle furnace and calcine at 900 °C for 10 h, cool to room temperature along with the furnace, and finally obtain a coated modified O3 phase material.
[0071] Step 4: Disperse sodium carbonate and ruthenium dioxide in a stoichiometric ratio of 3:1 in ethanol and stir for 1 hour;
[0072] Step 5: Weigh the materials in step 3 (i.e. the target coating layer Na3RuO4 and the O3 phase core material NaNi 0.5 Fe 0.4 Mn 0.1 O2 mass ratio), dispersed in the solution of step 4, stirred for 1 hour. Transferred to an oil bath pot and evaporated to dryness at 80℃, then taken out and dried in a vacuum drying oven at 60℃ overnight.
[0073] Step 6: Place the material in step 5 in a muffle furnace and calcine at 600 °C for 20 h to obtain an O3 phase positive electrode material with a double-layer coating, and the outermost coating layer is Na3RuO4.
[0074] Figure 1 This is the XRD diagram of the obtained double-layer coated O3 phase positive electrode material. It can be seen from the figure that the product is a pure O3 phase without obvious impurity peaks. After analysis, the reason why the coating layer phase is not reflected is because the coating amount is small.
[0075] Figure 2 This is a SEM image of the O3 phase positive electrode material with the obtained double-layer coating. It can be seen from the image that the positive electrode material is spherical and has a uniform coating layer.
[0076] In order to know the composition and structure of the coating layer 1, the coating layer 1 is prepared by the following method:
[0077] Step 1: Sodium carbonate, lithium carbonate, manganese carbonate and citric acid are weighed according to the molar ratio of Na, Li, Mn and citric acid of 0.39:1.02:0.03:0.03, and evenly dispersed in ethanol, stirred for 1 hour, transferred to an oil bath pot and evaporated at 80°C, then taken out and dried in a vacuum drying oven at 60°C overnight.
[0078] Step 2: The material in step 1 is placed in a muffle furnace and calcined at 900°C for 10 h, and then cooled to room temperature to obtain a coating layer 1.
[0079] The XRD pattern of the obtained coating material is as follows Figure 3 As shown, from Figure 3 It can be seen that the product is a mixed phase structure of spinel phase and tunnel phase, in which the coating layer is a mixed phase structure of spinel phase (111 peak) and tunnel phase; the characteristic peaks of the (350) crystal plane and the (140) crystal plane in the XRD diagram are magnified respectively, as shown in FIG. Figure 4 and Figure 5 As shown, and with the tunnel Na 0.44 Compared with MnO2, the characteristic peak of the coating material (350) crystal plane appears at a slightly lower 2θ angle, indicating that lithium ions mainly occupy the transition metal Mn site. + The strong polarity of Na leads to the expansion of the Na diffusion channel; 0.44 Compared with MnO2, the diffraction peak of the (140) crystal plane of coating layer 1 material appears at a slightly higher 2θ angle, indicating that Li in the lattice with a smaller atomic radius (≈0.76Å) successfully replaces Na (≈1.02Å). Combined with the raw material ratio, the chemical composition of the coating material is determined to be [Na 0.39 Li 0.05 ][Mn 0.03 Li 0.97 ]O2.
[0080] Example 2
[0081] Step 1: Sodium acetate, lithium acetate, manganese acetate and citric acid were weighed according to the molar ratio of Na, Li, Mn and citric acid of 0.4:0.98:0.06:0.06, dispersed evenly in ethanol, and stirred for 2 h.
[0082] Step 2: Weigh the O3 phase core material NaNi according to the coating ratio of 1% 0.5 Fe 0.4 Mn 0.1 O2 was dispersed in the solution of step 1, stirred for 2 h, transferred to an oil bath and evaporated at 120 °C, then taken out and dried in a vacuum drying oven at 80 °C overnight.
[0083] Step 3: The material in step 2 was placed in a muffle furnace and calcined at 950 °C for 12 h, and then cooled to room temperature to obtain [Na 0.4 Li 0.04 ][Mn 0.06 Li 0.94 ]O2 coated O3 phase material.
[0084] Step 4: Disperse sodium acetate and ruthenium dioxide in a stoichiometric ratio of 3:1 in ethanol and stir for 2 hours;
[0085] Step 5: Weigh the material in step 3 according to the coating ratio of 1%, disperse it in the solution of step 4, and stir for 2 hours. Transfer it to an oil bath pot and evaporate it at 120℃, then take it out and dry it in a vacuum drying oven at 80℃ overnight.
[0086] Step 6: Place the material in step 5 in a muffle furnace and calcine at 650 °C for 25 h to obtain an O3 phase positive electrode material with a double-layer coating.
[0087] Example 3
[0088] Step 1: Sodium acetate, lithium acetate, manganese acetate and citric acid were weighed according to the molar ratio of Na, Li, Mn and citric acid of 0.4:0.98:0.06:0.06, dispersed evenly in ethanol, and stirred for 2 h.
[0089] Step 2: Weigh the O3 phase core material NaNi according to the coating ratio of 0.5% 0.2 Fe 0.1 Mn 0.7 O2 was dispersed in the solution of step 1, stirred for 2 h, transferred to an oil bath and evaporated at 120 °C, then taken out and dried in a vacuum drying oven at 80 °C overnight.
[0090] Step 3: The material in step 2 was placed in a muffle furnace and calcined at 950 °C for 12 h, and then cooled to room temperature to obtain [Na 0.4 Li 0.04 ][Mn 0.06 Li 0.94 ]O2 coated O3 phase material.
[0091] Step 4: Disperse sodium acetate and ruthenium dioxide in a stoichiometric ratio of 3:1 in ethanol and stir for 2 hours;
[0092] Step 5: Weigh the material in step 3 according to the coating ratio of 1%, disperse it in the solution of step 4, and stir for 2 hours. Transfer it to an oil bath pot and evaporate it at 120℃, then take it out and dry it in a vacuum drying oven at 80℃ overnight.
[0093] Step 6: Place the material in step 5 in a muffle furnace and calcine at 650 °C for 25 h to obtain an O3 phase positive electrode material with a double-layer coating.
[0094] Example 4
[0095] Step 1: Sodium carbonate, lithium carbonate, manganese carbonate and citric acid were weighed according to the molar ratio of Na, Li, Mn and citric acid of 0.39:1.02:0.03:0.03, dispersed evenly in ethanol, and stirred for 1 h.
[0096] Step 2: Weigh the O3 phase core material NaNi according to the coating ratio of 0.5% 0.5 Fe 0.4 Mn 0.1 O2 was dispersed in the solution of step 1, stirred for 1 h, transferred to an oil bath and evaporated at 80 °C, then taken out and dried in a vacuum drying oven at 60 °C overnight.
[0097] Step 3: The material in step 2 was placed in a muffle furnace and calcined at 900 °C for 10 h, and then cooled to room temperature to obtain [Na 0.39 Li 0.05 ][Mn 0.03 Li 0.97 ]O2 coated O3 phase material.
[0098] Comparative Example 1
[0099] Step 1: Disperse sodium acetate and ruthenium dioxide in a stoichiometric ratio of 3:1 in ethanol and stir for 2 h;
[0100] Step 2: Weigh the O3 phase core material NaNi according to the coating ratio of 1% 0.5 Fe 0.4 Mn 0.1 O2 was dispersed in the solution of step 1 and stirred for 2 hours. The mixture was transferred to an oil bath and evaporated to dryness at 120°C, and then taken out and dried in a vacuum drying oven at 80°C overnight.
[0101] Step 3: Place the material in step 2 in a muffle furnace and calcine at 650 °C for 25 h to obtain Na3RuO4-coated O3 phase positive electrode material.
[0102] The positive electrode materials prepared in the above embodiments and comparative examples and the unmodified O3 phase NaNi 0.5 Fe 0.4 Mn 0.1 O2 is assembled into a battery, including:
[0103] First, the positive electrode material is mixed with acetylene black and polyvinylidene fluoride in N-methylpyrrolidone to form a slurry. Then, the slurry is coated on aluminum foil. The electrode is dried at 80°C in a vacuum drying oven for 12 h to obtain the positive electrode, and assembled into a button battery in a glove box. The button battery uses a GF / D diaphragm, a sodium sheet as the negative electrode, and a commercially available electrolyte. Its formula includes NaPF6 and a solvent. The concentration of NaPF6 in the electrolyte is 1 mol / L. The solvent includes PC (propylene carbonate), EMC (ethyl methyl carbonate) and FEC (fluoroethylene carbonate), wherein the volume ratio of PC to EMC is 1:1, and FEC accounts for 4% of the total volume of the solvent. The assembled battery is tested for electrical performance, with a charge and discharge voltage range of 2.0 to 4 V, a current density of 1C, and 50 cycles.
[0104] The positive electrode materials obtained in each embodiment and comparative example, and the unmodified O3 phase NaNi 0.5 Fe 0.4 Mn 0.1 The cycling performance results of the O2 assembled battery are shown in Figure 6As shown. After the positive electrode materials prepared in Examples 1-4 were assembled into batteries, the first cycle discharge capacity was 126.6 mAh / g, 123.4 mAh / g, 120.9 mAh / g and 117 mAh / g, respectively, and the capacity retention rates after 50 cycles were 92.65%, 90.76%, 88.09% and 81.79%, respectively. After the positive electrode materials prepared in Comparative Example 1 were assembled into batteries, the first cycle discharge capacity was 120 mAh / g, and the capacity retention rate after 50 cycles was 79.67%. The unmodified O3 phase NaNi 0.5 Fe 0.4 Mn 0.1 The first-cycle discharge capacity of the O2-assembled battery is 114.1 mAh / g, and the capacity retention rate after 50 cycles is 69.76%.
[0105] Combination Figure 6 The data show that compared with the unmodified cathode material NaNi 0.5 Fe 0.4 Mn 0.1 The battery assembled with Na3RuO4-coated modified positive electrode material showed higher specific capacity and better cycle performance. The reason may be that the material has 3 moles of sodium per unit molecular formula, which sacrifices itself at high potential and produces Na by oxidation decomposition. + ions, compensating for the sodium consumption caused by the formation of the positive and negative electrode interface film. For O3-type transition metal oxide positive electrode materials, additional sodium sources can ensure that the sodium ions in the lattice structure are not consumed, ensuring the stability of the positive electrode material, thereby showing good electrochemical performance in long-cycle tests; and Ru in Na3RuO4 is +5 valence, with a high covalent Ru-O bond and a high Na / Ru ratio. During the decomposition of sodium ions, the specific Na-O-Na configuration tends to form a non-bonded O 2p state, that is, a stable peroxide OO bond is formed during charge and discharge, which can effectively inhibit the collapse of the structure. And the double-layer coating structure can effectively play a variety of roles, not only can it better combine the advantages of O3, spinel phase and tunnel-type three-phase, improve the discharge specific capacity of the positive electrode material, accelerate the transmission rate of sodium ions, but also supplement sodium ions for the core material and enhance the cycle stability of the material.
[0106] Combination Figure 6 The data show that compared with the unmodified cathode material NaNi 0.5 Fe 0.4 Mn 0.1 The battery assembled with O2 and the battery assembled with the modified positive electrode material coated with the mixed phase material of spinel phase and tunnel phase showed higher specific capacity and better cycle performance. The reason may be that the tunnel phase has a special S-type structure, which is conducive to enhancing the Na + The diffusion dynamics of the spinel phase have three-dimensional Li +Diffusion channel, its theoretical capacity is high and the cost is low. + Replacement of Mn 3+ It can strengthen the crystal structure through Li-O bonds, provide a stable crystal framework, destroy the Mn-Mn interaction, and hinder the Mn 3+ disproportionation, reducing the Jiang Taylor distortion, thereby reducing the dissolution of Mn and extending the cycle life; and Figure 4 It can also be seen that the battery assembled with the positive electrode material modified by coating the mixed phase material of spar phase and tunnel phase has better cycle performance than the battery assembled with the positive electrode material modified by coating the mixed phase material of Na3RuO4, indicating that the coating modification of the mixed phase material of spar phase and tunnel phase is more effective in improving the structural stability of the positive electrode material during the electrochemical cycle.
[0107] Combination Figure 6 The data also show that the battery assembled with the positive electrode material first coated with the spinel phase and tunnel phase mixed phase material and then coated with Na3RuO4 has better discharge specific capacity and cycle performance than the battery assembled with the positive electrode material coated with a single Na3RuO4 or a single spinel phase and tunnel phase mixed phase material, indicating that the composite coating modification has a better modification effect.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified sodium ion battery positive electrode material, characterized in that: The invention comprises an O3 phase sodium transition metal oxide matrix and a coating layer 1 located on at least a part of the surface of the matrix, wherein the coating layer 1 has a tunnel phase and a spinel phase, and the chemical formula of the coating layer 1 is [Na x Li 0.44-x ][Mn y Li 1-y ]O2, wherein 0.39≤x≤0.4, 0.03≤y≤0.06, and also includes a coating layer 2, and the substrate, coating layer 1 and coating layer 2 are arranged in sequence from the inside to the outside; the coating layer 2 is Na3RuO4.
2. The modified sodium ion battery positive electrode material according to claim 1, characterized in that The chemical formula of the O3 phase sodium transition metal oxide matrix is NaNi a Fe b Mn 1-a-b O2, 0.2≤a≤0.5, 0.1≤b≤0.4; The mass of the coating layer 1 is 0.5-1% of the mass of the O3 phase sodium transition metal oxide matrix.
3. The modified sodium ion battery positive electrode material according to claim 2, characterized in that The mass of the coating layer 2 is 0.5-1% of the mass of the O3 phase sodium transition metal oxide matrix.
4. The method for preparing a modified sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that: include: S1. Add a sodium source, a lithium source, a manganese source and citric acid into ethanol and stir to obtain a solution A; In step S1, the molar ratio of sodium in the sodium source to lithium in the lithium source and manganese in the manganese source is 0.39-0.4:0.98-1.02:0.03-0.06; S2, adding O3 phase sodium transition metal oxide to solution A, stirring for a period of time, heating and stirring until the solvent is evaporated to obtain a solid, and drying the solid to obtain a mixture B; S3, sintering the mixture B at 900-950° C. to obtain a sodium ion battery positive electrode material coated with the coating layer 1; After step S3, the step of continuing in-situ coating of Na3RuO4 for modification is also included; The in-situ coating Na3RuO4 modification specifically includes: (1) Adding a sodium source and a ruthenium source into ethanol and stirring to obtain a solution C; (2) adding the modified sodium ion battery positive electrode material obtained in step S3 to solution C, stirring for a period of time, and then heating and stirring until the solvent is evaporated to dryness to obtain a solid, and drying the solid to obtain a mixture D; (3) calcining the mixture D to obtain a further modified sodium ion battery positive electrode material; the calcination temperature is 600-650° C.; and the calcination time is 20-25 h.
5. The method for preparing the modified sodium ion battery positive electrode material according to claim 4, characterized in that: In step S1, the molar amount of citric acid is 1 to 1.5 times the molar amount of the manganese source; The mass of the coating layer 1 is 0.5-1% of the mass of the O3 phase sodium transition metal oxide.
6. The method for preparing the modified sodium ion battery positive electrode material according to claim 4 or 5, characterized in that: In step S3, the sintering time is 10 to 12 hours.
7. The method for preparing the modified sodium ion battery positive electrode material according to claim 4 or 5, characterized in that: In step (1), the molar ratio of sodium in the sodium source to ruthenium in the ruthenium source is 3-3.3:1; In step (1), the mass of Na3RuO4 prepared by the sodium source and the ruthenium source is determined to be 0.5-1% of the mass of the O3 phase sodium transition metal oxide.
8. A sodium ion battery, characterized in that It includes the modified positive electrode material as described in any one of claims 1 to 3 or the modified positive electrode material prepared by the preparation method as described in any one of claims 4 to 7.
Citation Information
Patent Citations
Nickel-iron-manganese layered oxide positive electrode material and preparation method thereof
CN116364855A
Sodium-ion battery positive electrode material and preparation method and application thereof
CN117254012A
KR20220048912A